Use/Mention and Another Hot Mess - John Collins (Baltic International Yearbook of Cognition, Logic and Communication, 2026)
Azzouni seeks to identify and resolve a set of use/mention confusions both in general terms and especially as they arise in epistemology. The paper extends Azzouni's insights into linguistic theory, where similair confusions occur and which can be resolved in much the same terms as Azzouni proposes for epistemology.